Blue Light Hazard Optimization for High Quality White LEDs - Wei Tang; Jay Guoxu Liu; Chongyu Shen (IEEE Photonics Journal, 2018)
With the advanced formulation of new phosphors and latest progress in packaging design, technologies to obtain the higher color quality and healthier white LEDs are investigated. The luminescent properties were characterized by the spectrum power distribution (SPD) and IES TM-30-15. By engineering the SPD of white LEDs using advanced phosphor formulation and package design, we developed light sources that present qualities closest to daylight with higher color rendering index, better spectral continuity, and more nature color comparing to typical Ra80 LED on the market. It offers benefits that are not available in normal LED light sources, including minimized the potential blue hazard, improved color perception without drastically scarifying lumen efficiency, and reliability. The specific mechanism and relevant parameters of achieving high-quality white LEDs are investigated and analyzed in this paper.